Funcionamento metafórico e construção de identidades no discurso colonial britânico - Grigoletto, Marisa (Cadernos de Linguagem e Sociedade, 2010)
In 19th century British colonial discourse about India, figures of speech were found to be the principal mode of meaning production in a discourse that constructs an identity for the coloniser and the colonised. The analysis presented in this article claims that the figures of speech are responsible for an effect of “freezing” of meanings with the consequent characterisation of the colonised Indian as incapable of action and change and deprived of a history. This analysis challenges the traditional linguistic view that metaphors are ‘deviations’ from a literal, fixed meaning and argues in favour of a discursive perspective of the phenomenon, capable of producing a truly consistent understanding of the mechanisms of this specific type of colonial discourse.